Pengaruh Persepsi dan Religiusitas Santri Terhadap Minat Menabung di Bank Syariah - Heru Cahyono; Nur Muhammad Faiz Amin; Tarjono Tarjono; Agung Mardiansyah (Ecobankers : Journal of Economy and Banking, 2021)
This study aims to determine whether the perception and religiosity of the students of the Islamic boarding school of Tarbiyatul Banin, Kaliwadas sub- district, Sumber sub-district, Cirebon district have an effect on the interest in saving in Islamic banks. This research uses quantitative research. The data collection technique used a questionnaire with a Likert scale to obtain data on the influence of student perceptions (X1) and student religiosity (X2) on interest in saving in banks Islamic (Y). This study is a population study, taking data on MA level students with a total of 250 students, then the research sample is 30% of the total population with a total of 75 respondents using accidental sampling, observations and research were carried out by the author in January 2021. The results of this study indicate that there is a positive and significant influence on the perception and religiosity of the students of the Islamic boarding school of Tarbiyatul Banin, village of Kaliwadas, sub-district of Sumber, regency of Cirebon on the interest to save in Islamic banks. This can be proved by looking at the results of the F test which shows F count> F table, namely 29,990> 3.12 and a significance value of 0.000 <0.05 so that one can conclude that Ho is rejected and Ha is accepted. We can therefore conclude that there is a positive and significant influence between the perception and the religiosity of the students of the Islamic boarding school of Tarbiyatul Banin, Kaliwadas sub-district, Sumber district, Cirebon regency on the interest of saving in the Islamic banks. The implication of the research results shows that the perception and level of religiosity of students affects interest in saving in Islamic banks. Abstrak Penelitian ini bertujuan untuk mengetahui apakah persepsi dan religuisitas santri pondok pesantren tarbiyatul banin kelurahan kaliwadas kecamatan sumber kabupaten cirebon ini berpengaruh terhadap minat menabung di bank syariah. Penelitian ini menggunakan jenis penelitian kuantitatif. Teknik pengumpulan data dengan menggunakan kuesioner dengan skala likert untuk mendapatkan data pengaruh persepsi santri (X1) dan religuisitas santri (X2) terhadap minat menabung di bank syariah (Y). Penelitian ini merupakan penelitian populasi, dengan mengambil data santri tingkat MA dengan jumlah 250 santri, kemudian untuk sampel penelitian adalah 30% dari jumlah popolasi dengan jumlah 75 responden dengan menggunakan Accidental sampling, Observasi dan penelitian dilakukan dilakukan penulis pada bulan januari 2021. Hasil penelitian ini menunjukan bahwa terdapat pengaruh yang positif dan signifikan Persepsi dan Religiusitas Santri Pondok pesantren Tarbiyatul Banin Kelurahan Kaliwadas Kecamatan Sumber Kabupaten Cirebon terhadap Minat menabung di bank syariah. Hal ini dapat dibuktikan dengan melihat hasil uji F yang menunjukan F hitung > F tabel yaitu 29.990 > 3.12, dan nilai signifikansi 0.000 < 0.05 sehingga dapat disimpulkan Ho ditolak dan Ha diterima. Maka dapat disimpulkan bahwa terdapat pengaruh positif dan signifikan antara persepsi dan riliguisitas santri pondok pesantren tarbiyatul banin kelurahan kaliwadas kecamatan sumber kabupaten cirebon terhadap minat menabung di bank syariah. Implikasi hasil penelitian menunjukan bahwa persepsi dan tingkat religiusitas santri berpengaruh terhadap minat menabung di bank syariah.